Homens da fronteira:índios e capuchinhos na ocupação dos Sertões do Leste, do Paraíba ou Goytacazes: séculos XVIII e XIX - Malheiros, Márcia Fernanda Ferreira (2008)
This work deals with the social and interethnical relationships among indigenous groups,italian missionary capuchisn and other social actors present in the agricultural border expansion process in areas considered 'hinteland" called nowadays norte-noroeste fluminense during the XVIII e XIX centuries. In the second half of the XVIII century, this focused region was characterized by the colonial authorities like "Paraíba's hinteland", "Goytacazes' hinteland" or "wild Indians hinteland", because of its little colonial occupation and the majority presence of autonomous indigenous groups, remarkably the called Puri and Coroado, Macro-Jê trunk language spoken. In parallel to a new political and economical panorama marked by new guidelines in the indigenist policy, the mining falling in the captaincy of Minas Gerais and the expansion of sugar cane plantations and sugar mills in the baixada campista, this "hintelands" will attract settlers and authorities. in this process, the missionary agency wins relevance and will try the role of main mediator in the relationships among the indigenous groups, the settlers and the government. Even though the indigenist's cathechesis and civilization project, represented by São Fidélis, Itaocara and Santo Antônio de Pádua villages establishment, between 1781 and 1833, had earned special attention in this work, I pretend to deal in detail with the indigenous agency, your interests, strategy and actions, before significant changes deriving from the turnout of various social actors and agencies in the region.